An attempt to assess physical performance of male and female pupils who play selected musical instruments as compared to reference values of the Eurofit test battery provided by Dobosz - Apanowicz, Mateusz (Journal of Education, Health and Sport, 2018)
Introduction. The modern techniques of musical performance and occupational loading related to them require a comprehensive approach to the physical performance of players, their typical illnesses, physiotherapy and prophylaxis. Material and methods. 393 students from randomly selected music schools were qualified for the study. The level of physical fitness was assessed using the Eurofit test in each of the schools and the obtained test results were compared with the reference values provided by Dobosz. Summary The physical performance of female pupils of music schools was slightly higher than of male students. The physical performance at the age of 13, 14 and 18 was at a higher level than at the age of 11, 12, 15, 16 and 17 years. It was also significantly higher than the level represented by the peers in the area of flexibility, explosive and static strength, endurance of trunk muscles, agility and cardio-respiratory efficiency, but significantly higher within balance, functional endurance and the speed of upper limbs. As regards both girls and boys, the fittest pupils were among grand piano, violin and cello players, whereas accordion players turned out to be less fit and guitar players were even more unfit. 17-year-old violin players, 16-year-old guitar players and 12-year-old accordion players were reported to be the most unfit students. Among girls, the fittest pupils were observed in the group of accordion, grand piano, violin and cello players, while the most unfit individuals were 16-year-old guitar players and 17-year-old violin players. As regards boys, the fittest pupils were violin, grand piano and cello players and the most unfit ones were 12-year-old accordion players, 16-year-old guitar and cello players as well as 17-year-old violin players.